Rhizobium inoculation trials designed to support a tropical forage legume selection programme - Sylvester-Bradley, Rosemary (Springer, 1984)
Three phases of Rhizobium inoculation trials were carried out as part of a programme to select forage legume germplasm adapted to acid, infertile Oxisols of tropical America. Firstly, a range of tropical forage legumes were evaluated for their response to N fertilization or inoculation with strains previously shown to be effective in Leonard jars, using cores of undisturbed soil or in the field at Carimagua, Meta, Colombia. In pure legume stands onlyCentrosema macrocarpum andC. pubescens showed increases in N yield due to both inoculation and N fertilization;C. brasilianum responded only to N fertilization;Zornia latifolia, Z. brasiliensis andStylosanthes capitata responded to neither treatment. Trials in cores and in grass-legume mixtures showed responses ofDesmodium ovalifolium, Pueraria phaseoloides andS. capitata to N fertilization but not to inoculation. In the second phase of experiments strains were screened in soil cores with 16 ecotypes ofDesmodium, Centrosema, Stylosanthes andPueraria spp. Significant increases in N yield due to inoculation occurred with at least one strain in all the legumes exceptS. guianensis tardio , and in some trials withS. capitata. In the third phase of trials the most effective strains were tested in the field. Significant response ofP. phaseoloides andC. macrocarpum to inoculation at two sites and in the second year after establishment were shown. Further screening trials and field trials at different sites are needed in order to provide better recommendations for inoculation of grazing trials being set up in the region under study.